Big five inventory-version 10: a two-minute personality measurement tool in Urdu - Ahmad, Sabih; Sadiq Hussain (Journal of the Pakistan Medical Association, 2022)
Objective: To translate into Urdu and validate the Big Five Inventory 10. Method: The study was conducted at a tertiary care hospital in Kharian Cantonment, and a university in Gilgit, Pakistan, from October to December 2020. Online video meetings were held for the translation process related to the Big Five Inventory 10. A systematic six-step process was followed for translation and validation. The volunteers recruited for the pilot and validation phases were from various different administrative regions of the country. Factor analysis was performed to ascertain the construct validity, and Cronbach’s alpha was calculated to assess the reliability of the scale. Data was analysed using SPSS 23. Results: Of the 500 subjects, 358(71.6%) were males and 142(28.4%) were females. The overall age range was 18-48 years. The Urdu version was of the Big Five Inventory 10 was found to have a high level of construct validity supported by convergent and discriminant validity (p<0.05). The Cronbach alpha for all the sub-scales fell in the conventional range (0.71-0.88). Females scored higher on the ‘agreeableness’ subscale than the males (p<0.0). Conclusions: The Big Five Inventory 10 Urdu version was found to be a valid and reliable tool for researchers and clinicians having time constraints. Key Words: BFI-10, Urdu, Pakistan, Personality, Validation, Translation, Psychometric, Evaluation, Five factor model.